Relationship of Radiographic Osteoarthritis Severity with Treatment Outcomes after Imaging-Guided Knee Injections: A Prospective Outcomes Study - Miletic, Ivan; Agten, Christoph; Sutter, Reto; Pfirrmann, Christian; Peterson, Cynthia (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2018)
Introduction To be able to predict which patients are more likely to have a positive treatment outcome, the purpose of this study is 1: To compare outcomes after intra-articular corticosteroid knee injections with the Kellgren and Lawrence (KL) 5 and 3 grading systems for knee osteoarthritis, the Osteoarthritis Research Society International (OARSI) grading system and actual joint space measurements; and 2: To compare the reliability of these grading systems.Materials and Methods Knee radiographs of 117 patients who received intra-articular corticosteroid injections were independently evaluated by two radiologists blinded to the outcome. Evaluation included the KL5, KL3, OARSI systems and actual joint space widths. The numerical rating scale for pain was collected at baseline and along with the Patient’s Global Impression of Change on day 1, in week 1 and in month 1. The number of ‘improved’ patients was compared between the OA grades using the Chi-square test. Logistic regression determined which findings were predictive for improvement. Agreement was assessed using Kappa statistics and the intraclass correlation coefficient (ICC).Results Patients with OARSI grade 2 reported the highest rates of ‘improvement’ at all time points, which was significant on day 1 (p = 0.004). No relationship with improvement was found with KL5, KL3 or actual joint space measurements. Patients with OARSI grade 2 were 8 times more likely to report improvement on day 1 (p = 0.024). Reliability was best for joint space measurements (ICC = 0.812 – 0.882), followed by the OARSI.Conclusion The OARSI for joint space narrowing grade 2 (34 – 66 % narrowing) was linked with a better outcome on day 1 with trends in week 1 and month 1. The reliability of the OARSI was better than the KL5 or KL3 systems.Key Points Citation Format
Keywords: knee osteoarthritis; radiography; treatment outcomes; injections; intraarticular